2017
DOI: 10.1186/s12978-016-0266-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of the mistreatment of women during childbirth in health facilities in Guinea: a qualitative study with women and service providers

Abstract: BackgroundEvery woman is entitled to respectful care during childbirth; so it is concerning to hear of informal reports of mistreatment during childbirth in Guinea. This study sought to explore the perceptions and experiences of mistreatment during childbirth, from the perspectives of women and service providers, and the analysis presents findings according to a typology of mistreatment during childbirth.MethodsThis study used qualitative methods (in-depth interviews (IDIs) and focus group discussions (FGDs)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 12 publications
4
74
1
1
Order By: Relevance
“…High patient-to-provider ratios, and insufficient salaries for providers for long hours, overtime, and additional task were reported in our study, and these conditions may exacerbate frustration and stress of providers and constrain the provision of quality care. These findings are similar to a study in Guinea where it was reported that mistreatment occurred because providers were poorly trained and overworked [18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…High patient-to-provider ratios, and insufficient salaries for providers for long hours, overtime, and additional task were reported in our study, and these conditions may exacerbate frustration and stress of providers and constrain the provision of quality care. These findings are similar to a study in Guinea where it was reported that mistreatment occurred because providers were poorly trained and overworked [18].…”
Section: Discussionsupporting
confidence: 89%
“…The study used a mixedmethods design to understand and measure the mistreatment of women during childbirth in Myanmar, Nigeria, Ghana and Guinea. In the first phase, formative qualitative research was conducted to understand women's and providers' experiences and acceptability of mistreatment during childbirth [16][17][18][19][20][21]. The formative findings and systematic review [15] were used to inform the development of two measurement tools in the second phase (direct observations of labor and childbirth) and a community-based survey with women during the postpartum period in the same settings [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Negligent care (5), including lack of breastfeeding help and absence of a professional during delivery. Confidentiality and discrimination (6)…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have revealed and acknowledged disrespectful, offensive, and even negligent treatment of women during childbirth in health units in various parts of the world. [1][2][3][4][5] Several of these studies refer to physical violence, psychologic violence, verbal abuse, procedures performed without consent or with limited information, lack of privacy, and other non-recommended maternal care procedures. 6 Despite this evidence, a consensus on the way forward has not been reached at an international level.…”
Section: Introductionmentioning
confidence: 99%
“…23 Some of the contextual barriers-such as lack of respect and teamwork between obstetricians and midwives, heavy workloads, and challenges in maintaining continuity of labor monitoring and care by midwives-have been reported by health professionals in both high-and low/middleresource settings. [27][28][29][30] Although some of the health systems challenges may not be amenable in the short term, these findings provide a clear understanding of the potential obstacles that any labor monitoring tool must overcome to function in a real-life setting.…”
Section: Resultsmentioning
confidence: 96%